Experimental studies of e-contract establishment in the PL4BPM context. (21st June 2011) - Goncalves, Tiago Lopes; Gimenes, Itana Maria De Souza; Fantinato, Marcelo; Travassos, Guilherme Horta, Maria Beatriz Felgar De Toledo
Electronic contract (e-contract) establishment is a complex activity due to both sundry involved information and required parameters. PL4BPM, previously presented in other works, is an approach to support e-contract establishment and other activities related to business process management (BPM). It supports process reuse based on concepts of product line (PL) focusing on feature modelling to represent commonalities and variabilities of e-contracts. This paper complements the previous works with two experimental studies carried out to evaluate the e-contract establishment in PL4BPM context. The first study was undertaken within the academic environment and the second in the industrial one. Participants of both studies assessed the approach benefits over ad hoc procedures, especially focusing on its usability and feasibility. Both studies provide strong evidences of the advantages of PL4BPM approach over ad hoc approaches. The paper contributes to provide experimental data and process knowledge concerning approaches to e-contracts, business processes and related technologies.